An improved coefficient decimation based reconfigurable low complexity FIR channel filter for cognitive radios - Ambede, Abhishek (2013)
Multi-standard channel adaptation is a critical function in cognitive radio handsets which involves the transmission/reception of individual frequency channels of multiple wireless communication standards at different intervals of time. This needs dynamically reconfigurable, low complexity and high speed digital channel filters. In this paper, we present a reconfigurable finite impulse response (FIR) channel filter design technique based on the combination of the conventional coefficient decimation method (CDM) and a modified CDM. Our method enhances the frequency response flexibility of the filter and doubles the center frequency resolution when compared to the conventional CDM. The proposed channel filter has a significantly lower multiplication complexity and achieves superior stopband and transition band characteristics when compared to the channel filters based on the conventional CDM. Design example shows that a 57.1% reduction in multiplication complexity is achieved if the proposed channel filter is designed instead of the conventional CDM based channel filter.